PROBLEMS AND PROSPECTS OF DIGITAL ECONOMY DEVELOPMENT - Rakhmanbayeva Roza (Scholar Express Journals, 2025)
The article examines the world experience of digital economy development. the problems of converting information from product to product and the socio-economic consequences of this process require separate analysis and discussion. The development of digital technologies will be essential for achieving almost all economic and social goals and will affect all countries, industries and stakeholders. The digital economy requires a wide range of new knowledge and skills, significantly new social protection measures.
Keywords: digital economy; digital technologies; digital integration